Investigating Learners’ Experiences and Perspectives Towards the Distance Academic Interaction in Arabic Webinars - Muhammad Lukman Arifianto; Hanik Mahliatussikah; Wildana Wargadinata; Muh. Fuad Achsan (Ijaz Arabi Journal of Arabic Learning, 2022)
Since mid-2020, mostly caused by the Covid-19 outbreak which forced almost all academic activities involving massive participants to be cancelled due to health and safety reasons, the webinar suddenly became a very famous activity among learners. Therefore, this study aims to investigate the learners’ experience and perspective in this type of academic interaction, especially in Arabic webinar activity. Since this kind of interaction has become an upward trend that is applied massively by almost all institutions, observing it through a cross-sectional survey could be significant research. Thus, we use mixed (quantitative and qualitative-descriptive) methods to explore not only the perspectives of the participants but also to describe their experiences. It starts by providing data from survey results, classifying, analyzing, and presenting the analysis. Based on the recorded learners’ experience, it can be noticed that the Arabic webinars held by various Arabic language academies and institutions across the world were considered quite effective and efficient. Even though there are still many obstacles and shortcomings, especially from a technical point of view, this kind of web-based seminar can be one of the promising alternatives for Arabic learning when the Covid-19 pandemic is still ongoing. Most of the participants were satisfied with the performance of the Arabic language webinars they have participated in, indicated by a high score in the general assessment.